Assessment Of Antiarthritic Potential Of Carica Papaya L. Leaves Extract And Fractions: Histopathological Analysis (Journal of Pharmaceutical Negative Results, 2022)
Carica papaya L has been traditionally claimed for curing inflammation hence the present work exemplifies the anti-arthritic potential of crude leaves extract and its fractions in arthritic models. Screening on this plant has established presence of kaempferol which might possess antiarthritic properties. Kaempferol was quantitatively estimated by high performance thin layer chromatographic method in chloroform fraction and was found to be 0.08% w/w. Arthritis was induced by intraplantar administration considering formaldehyde (2%v/v), turpentine oil emulsion (10%v/v) and complete Freund’s adjuvant (1%v/v) in left hind paw of rats. Paw oedema, body weight, haematological parameters, level of serum enzyme markers, biochemical parameters, interleukin-6 and histopathological analysis were observed in all groups. Present experimental work justifies that in chronic arthritis, iinvolvement of interleukin-6 is associated with non-articular manifestations considering joint inflammation including anaemia. The plant extract and chloroform fraction possess dose dependent antiarthritic effect in acute and complete Freund’s adjuvant induced arthritic model by ameliorating the level of serum enzyme biomarkers, haematological and biochemical parameters, body weight abnormalities, interleukin-6. The experimental explanation established that extract and its fraction of Carica papaya L. revealed anti-arthritic potential.